LEGISLATION OF ISLAMIC LAW AND KHI - Faisal, Faisal; Nasution, Adelina (IAIN Tulungagung, 2021)
The struggle for the making Islamic family law after independence still leaves debate, for those who reject Islamic law legislation considers that Islamic law does not need to be included in state law, on the contrary for those who support it, consider that the state cannot ignore Islamic law in the state legal system. Marriage regulations are the initial stage of the Islamic law legislation process because it is not comprehensive enough that a presidential instruction on the Compilation of Islamic Law was issued in 1991. This article aims to analyze the roots of the struggle for marriage law legislation and the presence of KHI in Indonesia. This research resulted from a normative study with legal politics and a historical approach. This paper argues that the birth of KHI cannot be separated from the role of Muslim parties and the insistence of Islamic religious leaders who view that the marriage law is not comprehensive in regulating marriage law. The marriage law tends to ignore traditional fiqh and customary law, so the presence of KHI can eliminate the debate between the government and traditionalist Muslims.